Morocco : Second Review Under the Arrangement Under the Precautionary and Liquidity Line(PLL)-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Morocco's Second Review Under the Arrangement Under the Precautionary and Liquidity Line (PLL). Growth prospects for 2017 have improved, but nonagricultural growth is subdued. The current account deficit is projected to decline and international reserves are at a comfortable level. The IMF staff assesses that Morocco continues to meet the PLL qualification criteria and performs strongly in four out of the five areas of PLL qualification (external, monetary, financial, and data), does not substantially underperform in the fifth area (fiscal). The IMF staff recommends the completion of the second review under the PLL arrangement.